صلاحيات "مؤسسة ولي النانغرو" في ولاية آتشيه : راسة تحليلية في ضوء فقه السياسة الشرعية - ميسرة رحمي حسن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims to study the power of “Wali Nanggroe” Institution in Aceh: by looking at the perspective of Islamic Political Law. This Research explains the meaning of Aceh and the implementation of “Wali Nanggroe” institution in Aceh, its place, its job, the effect of dual power in Aceh, the powers of “Wali Nanggroe” institution in Aceh, and the opinions of Aceh community toward “Wali Nanggroe” institution”. The researcher adopted inductive methodology to gather all the information about the concept, the evidence, the rights of leader in Islam and other related topics; as well as an analytical approach in the presentation of information on the real fact. Data collection was conducted by meeting “Wali Nanggroe” institution in Aceh and some government departments that are related to this problem. The most important finding in this study is that “Wali Nanggroe” institution is one of the main culture's institution in Aceh which holds the role to keep the nature cultures and languages in Aceh. Although this institution is a non-government institution but some works of “Wali Nanggroe” institution has effected the dual power in Aceh in giving some rule in social matters, education division and economic division. In addition, the power of “Wali Nanggroe” institution in the light of its rights including the right of immunity, protocol, giving the opinion and advice to the government in Aceh, and has the right for financial as well. The most important power of this institution is to unity the community in Aceh. Another finding in the perspective of Islamic Political Law is that “Wali Nanggroe” institution is non-political institution. Hence, “Wali Nanggroe” cannot be similar like “Wali „Amr” in Islam, So, the compulsory to command “Wali Nanggroe” is not because of he is “ Wali „Amr” but because he is the leader of “ Wali Nanggroe” institution in Aceh which establishes to unite the Aceh community. Everything about the regulation of this institution written in law of Aceh, no. 8 of 2102, and Aceh government's law no. 9 of 2102 on some amendments about “Wali Nanggroe” institution in Aceh.